Angular structure of extragalactic radio sources at low frequencies - Brazhenko, A.I.; Koshovy, V.V.; Lozynsky, A.R.; Megn, A.V.; Rashkovsky, S.L.; Shepelev, V.A. (Кинематика и физика небесных тел, 2005)
The low frequency VLBI of URAN network operated in the decameter range has been designed in Ukraine to study cosmic radio sources. The network consists of five radio telescopes making up of four interferometers with baselines range from 42 to 913 km with UTR-2 radio telescope operated as the main antenna of the interferometers. The angular resolution of the network amount to 1 arcsec at the highest frequency of the range, and its sensitivity is about 20 Jy. Regular observations of galactic and extragalactic radio sources are performed with the network. Some results of studies are presented here.